Analisis Hubungan Dinamis Instrumen Kebijakan Moneter di ASEAN - M Rasyidin; M Saleh; Sri Hartati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The central bank as the monetary authority has the right to conduct monetary policy through setting monetary targets such as interest rates, controlling the money supply and stabilizing the inflation rate. The main objective of monetary policy is that its achievements can only be seen from a long-term perspective, meaning that everything is prepared now to achieve the main goals in the future. Monetary policy can be expansionary or contractionary. The linkage between policy instruments and the main targets through transmission channels is known as the monetary policy transmission mechanism. This study examines the dynamic relationship between monetary policy instruments in ASEAN. This research model uses VECM (Vector Error Correction Model) by testing Stationarity Test (Unit Root Test), Optimum lag selection and cointegration test. The results showed that not all ASEAN countries have a dynamic relationship between monetary policy instruments. Only Indonesia and Brunei Darussalem have dynamic relations between monetary instruments. While Laos only relates to money supply and interest rates, while the dynamic relationship between inflation and interest rates only occurs in the Philippines, other ASEAN countries such as Cambodia, Myanmar, Malaysia, Singapore, Thailand and Vietnam do not have a relationship between monetary policy instruments instruments.